Contextual Learning in Developing Self-Regulation and Discipline for the Practice of Islamic Values - Salwa; Atikah Salsabila; Didit Darmawan (Inspiratif Pendidikan, 2026)
This literature study aims to analyze the role of Contextual Teaching and Learning (CTL) in developing self-regulation and learning discipline and their contribution to the application of religious values in daily life. Using a qualitative library research approach, this study synthesizes concepts from various relevant theoretical sources. The findings indicate that CTL develops self-regulation and learning discipline through its seven components: constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. Self-regulation bridges religious knowledge with actual behavior through planning, implementation, and reflection phases. Learning discipline forms time structures and routines conducive to religious practice and builds consistent character that transfers to other life domains. The relationship between self-regulation, learning discipline, and value application is reciprocal and mutually reinforcing. CTL provides concrete experiences connecting these three domains, enabling Islamic Education to not only produce cognitive understanding but also form individuals capable of self-regulation, discipline, and consistent application of Islamic values in real life. This study implies the need to strengthen CTL implementation in Islamic Education and create supportive ecosystems through collaboration between teachers, schools, families, and communities. This literature study aims to analyze the role of Contextual Teaching and Learning (CTL) in developing self-regulation and learning discipline and their contribution to the application of religious values in daily life. Using a qualitative library research approach, this study synthesizes concepts from various relevant theoretical sources. The findings indicate that CTL develops self-regulation and learning discipline through its seven components: constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. Self-regulation bridges religious knowledge with actual behavior through planning, implementation, and reflection phases. Learning discipline forms time structures and routines conducive to religious practice and builds consistent character that transfers to other life domains. The relationship between self-regulation, learning discipline, and value application is reciprocal and mutually reinforcing. CTL provides concrete experiences connecting these three domains, enabling Islamic Education to not only produce cognitive understanding but also form individuals capable of self-regulation, discipline, and consistent application of Islamic values in real life. This study implies the need to strengthen CTL implementation in Islamic Education and create supportive ecosystems through collaboration between teachers, schools, families, and communities.